Correction: Seroepidemiology of hepatitis A, B, C, D and E virus infections in the general population of Peru: A cross-sectional study. - PLOS ONE Staff (PLoS ONE, 2021)
[This corrects the article DOI: 10.1371/journal.pone.0234273.].